Infeksi Cucumber mosaic virus dan Chilli veinal mottle virus pada Cabai di Kabupaten Rejang Lebong, Bengkulu - Mimi Sutrawati; Djamilah .; Andreani Kinata (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Mosaic disease caused by Cucumber mosaic virus (CMV) and Chilli veinal mottle Virus (ChiVMV) has been distributed widely in chilli in Indonesia and considered as important disease. A research was conducted to investigate the spread and incidence of CMV and ChiVMV in Rejang Lebong, Bengkulu and to identify its insect vector. Symptomatic and asymptomatic leaf samples were collected systematically from several chillipepper fields for further detection by DAS-ELISA (Double antibody sandwich-enzyme linked immunosorbant assay) using specific antibody for CMV and ChiVMV. The result showed that infection of both CMV and ChiVMV was found with disease incidence reached 20-50%, whereas infection only by ChiVMV or CMV were 50-80% and 20-50%, respectively. One species of aphid, i.e. Aphis gossypii was found from the fields.Key words: Aphis gossypii, CMV, ChiVMV, disease incidence